Estimating the impacts of climate change on Brazilian regions - Carlos Azzoni; Eduardo Haddad (European Regional Science Association (ERSA), 2011)
An integrated approach projects the economic impacts from climate change and adaptation and mitigation policies, explicitly considering the various territorial scales in Brazil (macro-regions, states, micro-regions, and networks of cities). A computable general equilibrium (GCE) model was used to simulate two climate change-free scenarios regarding the future of Brazil's economy that are consistent with the global economic development trends under IPCC's scenarios A2 and B2. Climate shocks, captured by the model through impacts on the agricultural/ livestock and energy sectors, were applied to these scenarios. The socio-economic trends of the scenarios with and without global climate change were reviewed in terms of benefits and costs for Brazil and its regions. The models interact with the agricultural/livestock and energy sector studies through variables such as energy generation and consumption for different sectors and regions, replacement of sources of energy in the production process and consumption by the residential sector, agricultural yields and land use, etc. These, in turn, are dependent on climate variables, future water supply and other economic factors.
Keywords: 330